Power : why some people have it--and others don't - Pfeffer, Jeffrey (New York, NY : HarperBusiness, 2010)
'The summa of one of the greatest minds in management theory, this book shows readers how to succeed and wield power in the real world'--
Includes bibliographical references and index.
Keywords: Success in business; Success; Management; Power (Social sciences)